Achalasia in Children and Adolescents. Issue 3 (September 2022) - Ambartsumyan, Lusine
Pediatric achalasia is a rare disorder of the esophagus that results in functional obstruction at gastroesophageal junction and impedes antegrade movement of bolus into stomach. Children present with vomiting/regurgitation, dysphagia, weight loss, and nocturnal and respiratory symptoms. Diagnosis may be delayed as symptoms mimic common pediatric disorders. Diagnosis follows adult diagnostic pathways yet remains challenging given absence of normative values in children. Treatment goals are to reduce symptoms, improve esophageal emptying, and prevent megaesophagus. Laparoscopic myotomy, pneumatic dilation, and peroral endoscopic myotomy are definite treatment options in children. Follow-up is necessary to monitor/treat reflux and complications, disease recurrence/persistence, and megaesophagus.